Innovation and education policies impact on knowledge based economies performance - Ala, Soraia (2015)
This paper uses publicly available data to identify the existence of a correlation, between the innovation and education performance of nations, and their Gross Domestic Product (GDP) output to stress that knowledge based economies exhibit higher performance. Although it is not consensual that from the array of public policies available to induce growth the ones fostering innovation are the ones that lead to higher growth, political leaders have been recognizing that, to increase competitiveness, economies need to change their development paradigm from one based on the exploitation of resources to a new one based on knowledge and innovation. To that end, public policies, need to focus on improving the quality of education, to strengthen research performance, to promote innovation and knowledge transfer, so that innovative ideas can be turned into new products and services that create growth, quality jobs and help address global societal challenges.